Students Perception Toward Cross Culture Understanding Thorouh Digital Literacy on Students English Department Universitas HKBP Nommensen Pematang Siantar - Asima Rohana Sinaga; Dumaris Silalahi; Christian Neni Purba; Apriana Sijabat (CV Putra Publisher, 2026)
This research aims at strengthening students’ character in Cross Culture Understanding thorough digital literacy at the fifth semester of Universitas HKBP Nommensen Pematangsiantar. The methodology of this research uses mix method design: Qualitative and Quantitative one. The participant of the research is the fifth semester of English Department of Universitas HKBP Nommensen Pematangsiantar, Group P1A1 and P1A2. The researcher assumes that students who possess strong digital literacy skills are better equipped to engage with diverse perspectives and develop their characters or empathy towards others. This proposal seeks to explore these relationships further, providing insights into how educational institutions can better support their students in these areas. This instrument of this Research is Questioners, and the documentation. The researcher will analyze the data from the questioners quantitatively by using SPSS 23 and qualitatively by descriptive documentation. This Research will produce as a book Cross Culture Understanding subject